RECENT GEOMORPHIC CHANGES AND ANTHROPOGENIC ACTIVITIES IN THE DELTAIC PLAIN OF PINIOS RIVER IN CENTRAL GREECE - Gaki-Papanastassiou, K.; Karymbalis, E.; Maroukian, H. (Bulletin of the Geological Society of Greece, 2010)
The Pinios river delta is a Late Holocene arcuate type delta, located in the southern Thermaikos gulf (Central Greece). In order to determine the processes which contributed in the recent configuration of the delta, a detailed geomorphic map at the scale of 1:5000 has been prepared showing both the deltaic plain and the coastal zone features using GIS techniques. Comparative examinations of aerial photographs taken in different dates and reliable maps of the last two centuries along with field observations depict recent changes of the delta morphology. The most important factors for the development of the delta are fluvial sedimentation, wave activity and longshore currents in a tectonically active area. Land uses throughout the delta plain have been mapped in an attempt to identify socio-economic activities. The dominant feature in the deltaic plain is the numerous abandoned meandering channels. The delta shoreline is generally retreating due to marine processes especially where former river mouths occur. Finally, various future sea-level rise scenarios have been analyzed and an assessment of the impacts of the potential global future sea-level rise to the delta is estimated.